The effectiveness of a manual handling workplace risk assessment team in reducing the rate and severity of occupational injury. - Carrivick, Philip (Curtin University, 2002)
Globally, there is an increasing tendency for occupational legislation and practice to require that employers actively involve their employees in the process of identifying, assessing and addressing the risk of injury in the workplace. Despite this, there is a paucity of research evaluating the effectiveness of participatory ergonomics in reducing occupational injury outcomes. In particular, a review of the literature fails to identify research that reports a change in the risk of injury at the level of the individual worker. The objectives of this study were to determine whether a participatory ergonomics approach to the control of workplace hazards and manual hazards in particular, could reduce the occurrence and severity of injury among a working population at risk.The research design was that of a longitudinal pre-post intervention study, with one intervention and three comparison groups. The observational period between 1 July 1988 and the 31 October 1995, comprised a 4.3 year pre-intervention period and a 3- year post-intervention period. The Intervention Group was a population of hospital cleaners at a high risk of injury. Three comparison groups were used, namely orderlies from the same hospital, cleaners from a similar hospital, and all the cleaners in the State of Western Australia. The primary outcome measure of occurrence was that of a lost- time injury (LTI).To obtain parameters of injury severity, each LTI was measured in terms of the associated CP1-adjusted workers' compensation claim cost and the number of hours lost from work (duration). The data were obtained three years after the observational period, to improve the likelihood that the claims had been finalised. Aggregate level LTI data were obtained for all four groups. Individual-level data were also obtained for the Intervention Group and the Orderly Services Group, whether injured or not. These data included the age, gender, hours worked and work experience of the subjects. Also, where there was an LTI, it was determined whether or not the mechanism of injury was from manual handling. Using these data, two analytical approaches were then undertaken. Study 1 assessed the aggregate-level LTI data of the four groups. Study 2 evaluated individual-level data for the Intervention Group and the Orderly Services Group.The results demonstrate statistically significant post-intervention reductions In all measures of LTI occurrence for the Intervention Group. In particular, after allowance for age, gender and work experience, there was a two thirds reduction in the rate of LTI per hour worked. No reduction in injury occurrence was observed for any of the comparison groups. The severity of each injury, as measured by claim cost and duration, did not change after the intervention for the Intervention Group.This study indicates that a small group of unskilled workers, with the facilitation of an ergonomist, can successfully undertake an iterative process of identifying and assessing hazards and make recommendations for their control. In doing so, even where the primary focus is on manual handling hazards, a reduction in the risk of injury from both manual handling and non-manual handling mechanisms can be achieved. Participatory ergonomics, by investing hazard management skills within employees, increases the likelihood that solutions to problems will be accepted, and should release ergonomists to consult to a greater number of workplaces than if they work independently of employee participation. The evaluation of interventions in a variety of workplace settings is recommended, to confirm participatory ergonomics as an effective tool for the reduction of the global burden of occupational injury.